2021
DOI: 10.1093/infdis/jiab265
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal Antibody Requires Immunomodulation for Efficacy Against Acinetobacter baumannii Infection

Abstract: Monoclonal antibodies (MAbs) are gaining significant momentum as novel therapeutics for infections caused by antibiotic-resistant bacteria. We evaluated the mechanism by which anti-bacterial MAb therapy protects against Acinetobacter baumannii infections. Anti-capsular MAb enhanced macrophage opsonophagocytosis and rescued mice from lethal infections by harnessing complement, macrophages, and neutrophils, yet the degree of bacterial burden did not correlate with survival. Furthermore, MAb therapy reduced pro-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…monoclonal antibody showed that the antibody's efficacy was linked to complement activation, and administration of the mAb led to increased serum levels of C3a consistent with synergistic activation of the classical pathway. This conclusion was further supported by reduced efficacy of the mAb in C3 knockout mice, indicating complement C3 acts in tandem with the humoral immune response to clear A. baumannii (46). Collectively, these data suggest that complement is not essential for antibody-mediated immunity but improves the host's capability to clear A. baumannii via opsonization and phagocytosis.…”
Section: Antibody-mediated Complement Activationmentioning
confidence: 80%
“…monoclonal antibody showed that the antibody's efficacy was linked to complement activation, and administration of the mAb led to increased serum levels of C3a consistent with synergistic activation of the classical pathway. This conclusion was further supported by reduced efficacy of the mAb in C3 knockout mice, indicating complement C3 acts in tandem with the humoral immune response to clear A. baumannii (46). Collectively, these data suggest that complement is not essential for antibody-mediated immunity but improves the host's capability to clear A. baumannii via opsonization and phagocytosis.…”
Section: Antibody-mediated Complement Activationmentioning
confidence: 80%
“…baumannii, dose-dependent bactericidal activity was observed (Figure S3). In contrast, such activity was not observed when using naïve serum or heat-inactivated serum, indicating that the effect could likely be attributed to complement activation. , Immunity against A. baumannii could also be established by intranasally administering Neu-NT (Figure c); the lower serum antibody titers compared with subcutaneous administration was likely due to the various mucosal barriers hindering delivery .…”
Section: Resultsmentioning
confidence: 98%
“…In contrast, such activity was not observed when using nai ̈ve serum or heat-inactivated serum, indicating that the effect could likely be attributed to complement activation. 34,35 Immunity against A. baumannii could also be established by intranasally administering Neu-NT (Figure 2c); the lower serum antibody titers compared with subcutaneous administration was likely due to the various mucosal barriers hindering delivery. 36 After confirming successful antibody titer generation, we sought to characterize the innate immune response elicited by Neu-NT in greater detail.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Particularly, numerous isolates from patients with A. baumannii infections definite surface capsular polysaccharides and contain a preserved gene group, called the K locus, which may regulate invention of capsular polysaccharides (Murray et al, 2020). An accidental transposon screening to recognize genes important for development in an incendiary exudative liquid principal to the proof of identity of the ptk and epsA genes, which are foretold to be required for capsule polymerization and assemblage (Nielsen et al, 2021).…”
Section: Lipopolysaccharides (Lps) and Capsular Polysaccharidesmentioning
confidence: 99%
“…Three important classes of enzyme, such as phospholipase C (PLC), phospholipase A (PLA) and phospholipase D (PLD) have been definite established on the cleavage location. PLA hydrolyzes fatty acids from the glycerol (Nielsen et al, 2021), while PLC chops the phosphorylated head collection from the phospholipid. PLD is a transphosphatidylase that only cleaves off the head cluster.…”
Section: Phospholipase Enzymementioning
confidence: 99%